Upaya pesantren dalam mengatasi problematika adaptasi santri baru di pondok pesantren kabupaten Tapanuli Selatan - Pane, Riem Malini; Lubis, Sufrin (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2024)
Islamic boarding schools with their characteristics are a major challenge for new students, starting from being separated from their parents, having binding rules, limited space for movement and various other problems. In this situation, it is not uncommon for new students to cause various problems that even make them desperate to move or even drop out of school. However, Islamic Boarding Schools in South Tapanuli Regency, were able to overcome these various problems as evidenced by the fact that out of 37 first-year students and 87 second-year students in one of the Islamic boarding schools, none were found to have moved or dared to drop out of school. This study aims to examine how Islamic boarding schools are able to overcome the problems of new students' adjustment and they are comfortable living in the Islamic boarding school. This study uses qualitative research with a field study approach. The results of this study indicate that in general, Islamic boarding schools make two efforts to overcome the problems of new students, namely preventive efforts (prevention) which are formulated into two major agendas in the form of intensive training for all educators and compiling supporting agendas, secondly repressive efforts (handling) through three stages, namely diverting with dormitory activities, involving counselors and involving parents and each has its own stages and descriptions.